The Life and Legacy of Khoja Ahmad Yasavi, The Sultan of The Arifs - Muminovich, Khoshimkhanov (Indonesian Journal Publisher, 2025)
This article also presents examples of Ahmad Yasawi’s life, the respect shown to him by the people, his writings and several examples of his poetic wisdom of a moral and universal nature. The article proves that the writer’s ideas were still important in the 12th century and are cited as an example in protecting people from various vices in today’s era of globalization. It is known that even in his time, Yassawi opposed various injustices of the kings and called on the people to be honest. It was analyzed that the works of this scholar are in accordance with the rules of Islam, and the ideas contained in them have not lost their significance even in modern science. For this reason, the Turkish Muslim people consider him a great teacher for them.